East Africa and oceanic exchange networks between the first and fifteenth centuries - Philippe Beaujard (Afriques)
From the second millennium BC, East Africa has been connected with oceanic exchange networks and has been included within an Afro-Eurasian world-system, where it formed a periphery from the beginning of the first millennium of the Christian Era, then a semi-periphery from the 10th century onward. As the various articles of this issue of the Journal Afriques show, although the East African coast has been oddly neglected by authors such as K. Chaudhuri (1975) and J. Abu-Lughod (1989), it did play an active role in the world-system, even after the arrival of the Portuguese during the 16th century.